Aahara and different Ayurvedic Aahara Upayoga Niyama: A narrative review - Upadhyaya, Nilkanth; Adhikari, Rameshwar (Journal of Ayurveda Campus, 2024)
Backround: Traya-Upastambha are Aahara (diet/food), Nidra (sleep), and Brahmacharya (following the path of God Brahma). Among them, Aahara has been placed first. The diet and its method of intake have an important role in the continuity of a healthy life. The rules and methods of dietary intake, the principle of Pathyapathya (wholesome & unwholesome diet), Ashta Aahara Vidhi Visheshaayatana, Dvadasha Asana Vidhi (discipline of twelve eating techniques), Viruddha Aahara (incompatible diet), etc. have been described in Ayurveda classics, and these are all vital in the maintenance of health as well as in curative aspects for many diseases. Hence, this review was aimed at highlighting the importance of Aahara and different Ayurvedic Aahara Upayoga Niyama described in different Ayurvedic classics. Materials and Methods: The classical literature of Ayurveda, like Samhitas contributed by Charaka, Sushruta, Vagbhata, Bhava Mishra, and others, along with various databases like PubMed, Google Scholar, etc., has been searched with the terms “Aahara” and dietetic concepts of “Aahara in Ayurveda.” Then data from Aahara and different Ayurvedic approaches to intake were qualitatively analysed and described to establish its importance in our daily lives. Results and Discussion: Aahara has one or more properties of Dosha aggravating, pacifying, or balancing action on physical and mental Dosha of human being. The qualities endowed to Aahara are only seen when rules and regulations regarding Aahara Sevana are followed. The contemporary modern science mainly described Aahara according to the nutritional value of its components, not like Hita, Ahita, Pathya, Apathya Aahara, etc. in a personalised manner. So, due consideration mentioned in Ayurveda should be given to all aspects of diet planning in the treatment of diseases and to maintain the health of the individuals. Conclusion: The diet and its method of intake have an important role in the daily life for promotion of positive health and continuity of a healthy life. The benefits of Aahara can be achieved only by following the healthy dietary guidelines. Therefore, one should try and follow the rules and methods of dietary intake for the maintenance of health as well as in curative aspects for many diseases.